Structural aspects of the regulation of Parkinson's Disease-associated LRRK2 Kinase by Rab GTPases - MCGRATH, EMMA MARGARET (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2019)
The Rab family of small GTPases are the premier organisers of endocytic and secretory pathways in cells. They behave as molecular 'on/off' switches and in their active GTP-bound state recruit soluble effector proteins to coordinate sequential trafficking events. In recent years, Rab GTPases have been identified as key players in Leucine-rich repeat kinase-2 (LRRK2)-mediated signalling pathways. LRRK2 is a large multi-domain protein containing an enzymatic GTPase and kinase core surrounded by multiple accessory domains. Mutations in LRRK2 are found to be a significant risk factor for both heritable and sporadic development of Parkinson's disease, and typically result in the over-activation of the kinase domain. LRRK2 phosphorylates a subset of Rabs including Rab8, Rab10 and Rab12 in the Switch 2 helix and modifies their interactions with effectors and regulatory proteins. This activity is regulated upstream by Rab29, which recruits LRRK2 to Golgi compartments via it N-terminus and activates the kinase domain. Furthermore, the related Rab32-subfamily GTPases, Rab32 and Rab38, also interact with the N-terminus and are important for the localisation and trafficking of LRRK2 in cells. The N-terminus of human LRRK2 begins with armadillo repeat motifs (ARM) followed by ankyrin repeats (ANK), however the molecular basis of LRRK2:Rab complex interactions within these domains is currently unknown. Here we show that all members of the Rab32-subfamily bind to an identical site within the ARM domain of LRRK2. Biophysical analyses reveal affinities in the low micromolar range and complex formation is GTP- dependent. The crystal structures of uncomplexed Rabs suggest residues within the switches that likely mediate interactions with LRRK2, and mutational analyses reveal a positively charged residue in Switch 1 is critical for binding of Rab32/38. However, the equivalent mutation in Rab29 is dispensable for the interaction. Furthermore, homology modelling and mutational studies of the LRRK2 ARM domain identify a negatively-charged surface that represents the Rab binding site. These structural and biochemical studies provide insight into the molecular interactions between LRRK2 and Rab GTPases, and raise interesting questions concerning the regulatory functions of Rab29 versus Rab32/38 in mammalian cells and their role in Parkinson's disease.
APPROVED
Keywords: Membrane Trafficking; Parkinson's Disease; LRRK2; Leucine-rich repeat kinase 2; Rab GTPases